Differential TNF-Signaling in Chronic Inflammatory Disorders - Holtmann, Martin H.; Neurath, Markus F. (Current Molecular Medicine, 2004)
TNF-α is a pleiotropic cytokine with strong proinflammatory and immunomodulatory properties. TNF-α plays a critical role in many acute or chronic inflammatory diseases and anti-TNFstrategies have proven to be clinically effective. Two TNF-specific cell surface receptors TNF-R1 and TNF-R2 have been identified and the function of these receptors and the downstream intracellular signal transduction pathways have been extensively studied in vitro. For a long time TNF-R1 was considered to be the predominant mediator of TNF-signaling, whereas TNF-R2 was ascribed only auxilliary function. However, there is increasing clinical and experimental evidence for an important independent role of p80 signaling in chronic inflammatory conditions. It is conceivable that the multiple TNF-mediated chronic inflammatory disorders differ in terms of the ligand form (soluble TNF-α versus membrane bound TNF-α), the receptor (TNF-R1 versus TNF-R2) and the downstream signaling cascades utilized. The elucidation of the specific characteristics of TNF-signaling in distinct inflammatory disorders will lead to a better understanding ot the pathogenesis of these diseases and will be the basis for the development of more specific and more efficient therapeutic approaches.
Keywords: inflammatory disorders